Rib fixation in non–ventilator-dependent chest wall injuries: A prospective randomized trial. Issue 6 (25th June 2022) - Marasco, Silvana Francesca; Balogh, Zsolt J.; Wullschleger, Martin E.; Hsu, Jeremy; Patel, Bhavik; Fitzgerald, Mark; Martin, Kate; Summerhayes, Robyn; Bailey, Michael
Abstract : BACKGROUND: The aim of this study was to assess pain and quality of life (QoL) outcomes in patients with multiple painful displaced fractured ribs with and without operative fixation. Rib fractures are common and can lead to significant pain and disability. There is minimal level 1 evidence for rib fixation in non–ventilator-dependent patients with chest wall injuries. We hypothesized that surgical stabilization of rib fractures would reduce pain and improve QoL during 6 months. METHODS: A prospective multicenter randomized controlled trial comparing rib fixation to nonoperative management of nonventilated patients with at least three consecutive rib fractures was conducted. Inclusion criteria were rib fracture displacement and/or ongoing pain. Pain (McGill Pain Questionnaire) and QoL (Short Form 12) at 3 and 6 months postinjury were assessed. Surgeons enrolled patients in whom they felt there was clinical equipoise. Patients who were deemed to need surgical fixation or who were deemed to be too well to be randomized to rib fixation were not enrolled. RESULTS: A total of 124 patients were enrolled at four sites between 2017 and 2020. Sixty-one patients were randomized to operative management and 63 to nonoperative management. No differences were seen in the primary endpoint of Pain Rating Index at 3 months or in the QoL measures. Return-to-work rates improved between 3 and 6 months, favoring the operative group. CONCLUSION: In this study, no improvements in pain or QoL at 3 and 6 months in patients undergoing rib fixation for nonflail, non–ventilator-dependent rib fractures have been demonstrated. LEVEL OF EVIDENCE: Therapeutic/Care Management; Level II. Abstract :